"One Fish, Two Fish, Red Fish, Blue Fish": How ethical beliefs influence consumer perceptions of "blue" aquaculture products?. (October 2019) - Banovic, Marija; Reinders, Machiel J.; Claret, Anna; Guerrero, Luis; Krystallis, Athanasios
Highlights: Cross-cultural survey to show impact of ethical beliefs on consumer perceptions. Ethical beliefs positively affect perceived product quality, value, and trust. Consumer involvement has limited moderation effect. Stable and reliable standards to increase consumers' trust in aquaculture products. Abstract: Respecting ethical beliefs of consumers is an important precondition for food manufacturers in their attempt to improve their positioning in the European food market. Based on a cross-cultural survey of 2511 European participants, this research demonstrates how ethical beliefs affect consumer perceptions of "blue" (i.e. environmentally friendly) aquaculture products. The study further emphasises that the positive effect of ethical beliefs on purchase intention operates via an indirect route mediated by consumers' trust in a product category. Consumer involvement has limited moderation effect on the above relationships. To expand its "blue" business, a key policy recommendation to aquaculture product manufacturers and policy makers is to urge stable and reliable standards of control in environmentally responsible aquaculture production so that consumers can rely on the information source and increase their trust in aquaculture products.